2021
DOI: 10.33134/njmr.377
|View full text |Cite
|
Sign up to set email alerts
|

Downward Professional Mobility among Poles Working and Living in Norway

Abstract: This article explores the diverse trajectories of downward professional mobility as experienced by skilled Polish migrants living in Norway. On the basis of 30 in-depth qualitative interviews with Poles who have worked below their level of competence after migrating to Norway, I outline (1) how they tend to channel themselves into low-skilled employment at the initial stages of migration as they commonly assume it is inevitable when migrating, and (2) how they interpret and respond to remaining in low-skilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Regarding social class, Poles in Norway find themselves in the working class and are often in the very lowest echelons of this. Moreover, many experience downward social mobility -compared to their homeland situationregarding education and work (Rye 2019;Przybyszewska 2021).…”
Section: I) the Pole As 'The Labor Migrant'mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding social class, Poles in Norway find themselves in the working class and are often in the very lowest echelons of this. Moreover, many experience downward social mobility -compared to their homeland situationregarding education and work (Rye 2019;Przybyszewska 2021).…”
Section: I) the Pole As 'The Labor Migrant'mentioning
confidence: 99%
“…They seek to avoid both the material aspects of working-class jobs, such as hardwork and low wages, but as much the low social status and stigma attached to these positions in the labor market. Several authors (Dyrlid 2017;Przybyszewska 2021;Stachowski 2021) have shown how Polish migrants continuously engage in such identity management, demonstrating how the 'labor migrant' label becomes both confirmed and contested. Looking for work, they benefit from the good reputation of the Polish work ethic and find manual work that is economically attractive relative to opportunities in Poland -albeit work that often implies downward professional mobility.…”
Section: Iii) Negotiation Of Polishnessmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the influx of highly qualified specialists has revealed a problem such as discrimination in the national labor market or the inability to obtain a vacant position in accordance with their qualifications, i.e., the problem of top-down qualifications (see Przybyszewska 2021) or overqualification (see Mukomel 2020), which ultimately leads to the depreciation of higher education or academic degree received by immigrants. Constantly, immigrants who cannot find a job that corresponds to their high academic and professional qualifications lose the right to claim a privileged status based on their skills, knowledge and qualifications.…”
Section: Contemporary Challenges: Talents In Educational Systems Reso...mentioning
confidence: 99%
“…Samtidig kan innvandrere eller transnasjonale migranter som skifter mellom heimlandet og nytt vertssamfunn oppleve å vaere i både multilokale, ustabile og inkonsistente klasseposisjoner (Rye, 2019). Polske migranter er ofte eksempel på middelklassetilhørighet i heimlandet og en mer prekaer posisjon i mottakerlandet (Przybyszewska, 2020;Rye, 2019). Mobilitet mellom ulike lokaliteter, og ulike sosiale praksiser i ulike lokaliteter, kan også bety at migranter beveger seg i ulike klassestrukturer, eksempelvis som hytteeiere et sted og fastboende et annet (Rye, 2011a).…”
Section: Klasse Makt Og Ulikhetunclassified